2002
DOI: 10.1029/2001je001614
|View full text |Cite
|
Sign up to set email alerts
|

Apollo 17 landing site: Topography, photometric corrections, and heterogeneity of the surrounding highland massifs

Abstract: [1] A high-resolution digital elevation model for the Apollo 17 landing site (20°N, 31°E) and surrounding region is used to correct the photometry of Clementine ultraviolet-visible multispectral data to standard viewing and illumination geometry on a pixel-by-pixel basis. FeO and TiO 2 concentrations were derived from these topographicphotometrically corrected data, and steep-sloped highland massifs are used to assess the magnitude of the effects of the correction. The effects are significant, yielding errors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…Mechanical separation of grains by composition is not unknown. On the Moon, lower reflectance material found in valleys and draws between massifs north ofthe Apollo 17 landing site are proposed to represent the preferential downslope movement of a mafic component of the regolith (Lucchitta, 1972;Robinson and Jolliff, 2002). Grain separation on Eros has been proposed to explain the anomalous color (Robinson et al, 2001) and geochemical properties (Evans et al, 2001) of the unusual ponded deposits (which show similar color trends to the highreflectance streaks), and a related mechanism may be at work here.…”
Section: Downslope Movementmentioning
confidence: 99%
“…Mechanical separation of grains by composition is not unknown. On the Moon, lower reflectance material found in valleys and draws between massifs north ofthe Apollo 17 landing site are proposed to represent the preferential downslope movement of a mafic component of the regolith (Lucchitta, 1972;Robinson and Jolliff, 2002). Grain separation on Eros has been proposed to explain the anomalous color (Robinson et al, 2001) and geochemical properties (Evans et al, 2001) of the unusual ponded deposits (which show similar color trends to the highreflectance streaks), and a related mechanism may be at work here.…”
Section: Downslope Movementmentioning
confidence: 99%
“…Determination of absolute TiO 2 content at high resolution ($200 m) for areas with significant local topographic variation within the central peaks is thus constrained by lack of accurate reflectance measurements and the absence of high resolution topographic data (Lucey et al, 1998;Jolliff, 1999;Robinson and Jolliff, 2002). The extent of topography related errors are also sensitive to latitudinal variations (Lucey et al, 1998) as this leads to change in sun angle.…”
Section: Analytical Approachmentioning
confidence: 98%
“…However, it should be noted that the plagioclase-rich fragments analyzed in this work were selectively sampled and therefore should not be expected to yield similar results to previous studies based on bulk compositional data (Rhodes et al 1974;Simon et al 1981;Korotev and Kremser 1992). Due to the known lithologic complexity of the Sculptured Hills (Robinson and Jolliff 2002), and the plagioclase-rich fragments targeted for analysis, it is not surprising that the eleven plagioclase-rich lithic fragments were strongly biased against mare basaltic fragments.…”
Section: Origin Of the Plagioclase-rich Fragmentsmentioning
confidence: 99%
“…One of the prominent geological features of the valley is the highland unit found near the north massif, the Sculptured Hills. Apollo 17 astronauts sampled the regolith at the base of the Sculptured Hills during their last surface traverse at station 8 (latitude 20.278°N, longitude 30.848°S; Robinson and Jolliff 2002). They dug a 25-cm-deep trench (Wolfe et al 1981) that revealed the best preserved lunar regolith stratigraphy collected during the Apollo missions (Mitchell et al 1973; Fig.…”
Section: Regolith Sample Collected At Station 8 Apollo 17mentioning
confidence: 99%